2021
DOI: 10.1111/andr.13082
|View full text |Cite
|
Sign up to set email alerts
|

Intrasurgical parameters associated with successful sperm retrieval in patients with non‐obstructive azoospermia undergoing salvage microdissection testicular sperm extraction

Abstract: Background: Patients with non-obstructive azoospermia with a previously failed conventional testicular sperm extraction may undergo a salvage microdissection testicular sperm extraction with the probability of successful sperm retrieval being almost dependent upon the number of previous surgical attempts and to different histopathologic categories. Objectives: To determine whether the seminiferous tubules pattern and the histological categories could affect the sperm retrieval rate in patients with non-obstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…However, the prospective nature of the current work adds strength to the current findings in contrast to the retrospective studies conducted by Caroppo et al (2019) and (2021) [ 20 , 21 ]. Also, the sample size was larger than the 2 aforementioned studies.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…However, the prospective nature of the current work adds strength to the current findings in contrast to the retrospective studies conducted by Caroppo et al (2019) and (2021) [ 20 , 21 ]. Also, the sample size was larger than the 2 aforementioned studies.…”
Section: Discussionmentioning
confidence: 53%
“…Notably, they used that same magnification power (× 24) to evaluate the seminiferous tubules like ours in the current study [ 20 ]. Additionally, Caroppo et al (2021) conducted another retrospective study on 79 salvage NOA patients who underwent micro-TESE using a higher magnification power (× 36) to evaluate the seminiferous tubules [ 21 ]. They stated similar findings delivered out by their previous study [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from Xu et al [ 51 ] confirmed that HS associates with high SRR (85%) even in patients with previous sperm retrieval attempts, but found lower SRR in patients with SCO (5.5%) and MA (25%) compared to previous reports. Very recently, our group found that early and late MA were associated with the lowest probability of SSR (8.7 and 11.1%, respectively), while sperm was retrieved in 85% of men with HS; SRRs in patients with SCO differed significantly according to the presence (focal SCO) or not (complete SCO) of residual areas of HS (SRR 100% vs. 24.4%, respectively) [ 52 ].…”
Section: Testis Histologymentioning
confidence: 99%